Conditional Depletion of the Chlamydomonas Chloroplast ClpP Protease Activates Nuclear Genes Involved in Autophagy and Plastid Protein Quality Control. Issue 5 (30th May 2014) - Ramundo, Silvia; Casero, David; Mühlhaus, Timo; Hemme, Dorothea; Sommer, Frederik; Crèvecoeur, Michèle; Rahire, Michèle; Schroda, Michael; Rusch, Jannette; Goodenough, Ursula; Pellegrini, Matteo; Perez-Perez, Maria Esther; et al.
Abstract : Conditional depletion of the chloroplast protease ClpP in the alga Chlamydomonas affects plastid protein homeostasis and leads to an autophagocytic and plastid unfolded protein-like response. It involves vacuolization of the cytoplasm and increased accumulation of small heat shock proteins, specific chaperones, proteases, and proteins implicated in thylakoid membrane maintenance and biogenesis. Abstract: Plastid protein homeostasis is critical during chloroplast biogenesis and responses to changes in environmental conditions. Proteases and molecular chaperones involved in plastid protein quality control are encoded by the nucleus except for the catalytic subunit of ClpP, an evolutionarily conserved serine protease. Unlike its Escherichia coli ortholog, this chloroplast protease is essential for cell viability. To study its function, we used a recently developed system of repressible chloroplast gene expression in the alga Chlamydomonas reinhardtii . Using this repressible system, we have shown that a selective gradual depletion of ClpP leads to alteration of chloroplast morphology, causes formation of vesicles, and induces extensive cytoplasmic vacuolization that is reminiscent of autophagy. Analysis of the transcriptome and proteome during ClpP depletion revealed a set of proteins that are more abundant at the protein level, but not at the RNA level. These proteins may comprise some of the ClpP substrates. Moreover, the specific increase in accumulation, both at the RNA and protein level, of small heat shock proteins, chaperones, proteases, and proteins involved in thylakoid maintenance upon perturbation of plastid protein homeostasis suggests the existence of a chloroplast-to-nucleus signaling pathway involved in organelle quality control. We suggest that this represents a chloroplast unfolded protein response that is conceptually similar to that observed in the endoplasmic reticulum and in mitochondria.